Dimensions of storytelling in German literature and beyond : "for once, telling it all from the beginning" - Boney, Kristy Rickards; William, Jennifer Marston (2018)
"While Walter Benjamin, in his famous essay "The Storyteller" (1936), lamented the decline of the storytelling tradition in the age of the modernist novel, Anna Seghers and other twentieth-century German writers went on to chronicle the century's darkest days in creative and compelling ways. This volume is at its heart a tribute to Germanist Helen Fehervary, whose work, particularly on the prose of Anna Seghers, continues to inspire scholars who examine narration and storytelling. The subtitle quotation, "for once, telling it all from the beginning," is a translation of the phrase "einmal alles von Anfang an erzählen," from Seghers's exile novel Transit, in which she told not only her own story but that of countless others who faced existential challenges in their attempts to escape the Nazi regime. This volume examines a number of such writers, exploring the tensions between aesthetics and politically conscious writing, as well as individual struggles involving conformity and resistance in a totalitarian state